2014
DOI: 10.1073/pnas.1305609111
|View full text |Cite
|
Sign up to set email alerts
|

Maternal tract factors contribute to paternal seminal fluid impact on metabolic phenotype in offspring

Abstract: Paternal characteristics and exposures influence physiology and disease risks in progeny, but the mechanisms are mostly unknown. Seminal fluid, which affects female reproductive tract gene expression as well as sperm survival and integrity, provides one potential pathway. We evaluated in mice the consequences for offspring of ablating the plasma fraction of seminal fluid by surgical excision of the seminal vesicle gland. Conception was substantially impaired and, when pregnancy did occur, placental hypertrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
316
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 317 publications
(341 citation statements)
references
References 48 publications
8
316
1
3
Order By: Relevance
“…More recently a direct contribution of the father has been shown to influence the metabolism of offspring. Male rats fed a high fat diet give rise to female offspring with β-cell dysfunction [33], while our own studies provide evidence that male mice devoid of seminal plasma give rise to male offspring with altered metabolic profiles and increased fat accumulation [13].…”
Section: Early Origins Of Adult Disease and Foetal Programmingmentioning
confidence: 69%
See 3 more Smart Citations
“…More recently a direct contribution of the father has been shown to influence the metabolism of offspring. Male rats fed a high fat diet give rise to female offspring with β-cell dysfunction [33], while our own studies provide evidence that male mice devoid of seminal plasma give rise to male offspring with altered metabolic profiles and increased fat accumulation [13].…”
Section: Early Origins Of Adult Disease and Foetal Programmingmentioning
confidence: 69%
“…In female mice mated to males devoid of seminal plasma expression of embryotrophic factors in the oviduct is reduced while the pro-apoptotic factor Trail is increased. In addition embryos derived from these matings display perturbations in blastocyst formation which can be partially rescued using in vitro culture [13]. A definitive study by Sjoblom et al has demonstrated that addition of GM-CSF into culture media can alleviate some of the detrimental effects of embryo culture on pregnancy outcomes, such as altered placental morphogenesis [47].…”
Section: Pre-implantation Embryo Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…4,[6][7][8][9][10][11][12][13] It is also increasingly becoming apparent that the environmental state of both the mother and father can underpin later diseases in offspring, even those who appear healthy at birth. [14][15][16][17][18][19][20][21][22][23][24][25][26] Such intrinsic and extrinsic factors in animal models and humans include exposure to endocrine disrupting chemicals, such as bisphenol A, phthalates, heavy metals, stress, obesity, high fat/ high caloric diets, metabolic status and starvation conditions to provide a few examples. It is also clear that in general, males may be at greater risk for later disorders, including those of the cardiovascular and neurological systems, than females.…”
Section: Introductionmentioning
confidence: 99%